Children's experiences with a transmedia narrative: Insights for promoting critical multimodal literacy in the digital age. (October 2021) - Djonov, Emilia; Tseng, Chiao-I; Lim, Fei Victor
Abstract: Children's engagement with transmedia narratives, where the same story is presented through different media such as book, film and interactive app, can reveal their knowledge about different modes, media and software for multimedia authoring. Such insights provide a suitable starting point for developing effective approaches to critical multimodal literacy education in the digital age. Specifically, they can inform decisions about which concepts and frameworks for the critical multimodal analysis of texts and digital technologies to adapt for use with young learners. We advance this argument through a case study comprising: the transmedia narrative The Fantastic Flying Books of Mr Morris Lessmore in its film (Joyce and Oldenburg, 2011 ), interactive app (Moonbot Studios, 2011 ), and traditional picture book (Joyce, 2012) formats; observations of mothers and their 4–5-year-old children's interaction with the book and the app; a comic strip and a LEGO animation created respectively by a 7-year-old (Oskar) and a 10-year-old (Ollen), which represent a scene from that narrative; and. an interview with Ollen about his experience of making the animation with the software tools Stop Motion Studio and GarageBand '08. The case study's findings reveal: preschool-aged children's awareness of media affordances and semantic patterns in narrative. the older children's understanding of narrative conventions and capacity to construe broad social themes by selecting the most apt semiotic resources available in their chosen media. the ways both familiarity with different digital semiotic technologies and non-digital resources (e.g. LEGO) and a software's design can shape a child's multimedia authoring. Drawing on these findings, we argue that observations of children's experiences with transmedia narratives provide a suitable starting point for developing effective approaches to critical multimodal literacy education in the digital age. We posit that such observations can help educators consider which concepts and frameworks for the critical multimodal analysis of texts and digital technologies to adapt for use with young learners in the classroom. This necessarily involves examining continuity and change across old and new technologies and semiotic practices.